Keefektifan Pemberian Nebulizer Terapi Combivent Dan Terapi Bisolvon Terhadap Patensi Jalan Nafas Pada Pasien Asma Bronkial Diruang IGD BBKPM Makassar - Siti Lestari; Siti Handayani; Herman Bakri (Poltekkes Kemenkes Surakarta, 2018)
Abstract Background : Asthma is a worldwide health problem. People with asthma in the world today was estimated at 300 million peoples, and expected in 2025 reached 400 million peoples. In Indonesia, there were currently about 12.5 million peoples. In BBKPM Makassar, the number of people with asthma who visit in 2009 were 291 patients, in 2010 to 292 patients, and in 2011 starting from January to November, as 243 patients. It shows the number of people with asthma who visit the BBKPM Makassar each month has increased. Therapy of asthma treatment often used was nebulizer using combivent and bisolvon. Purpose this study to determine the effectiveness of provision nebulizer of combivent and bisolvon therapy to airway patency in asthma bronchial patient at ER of BBKPM Makassar. Method: used was quase experimental with two groups pretest and posttest design. Sample of 40 patients who met the criteria were randomly selected to be divided into two groups, 20 samples for nebulizer of combivent therapy, and 20 samples for nebulizer of bisolvon therapy. Method: Technique of data analysis used was paired t test. the Research result conducted on two groups of respondents, obtained t count value frequency of respiratory and pulmonary physiology in the treatment group of nebulizer using combivent obtained t count of the frequency of respiratory physiology was 15.601 and pulmonary physiology was 23.083, while the treatment groups of nebulizer using bisolvon obtained t count value was 7.701 and pulmonary physiology was 12.606. Result: were both higher than the t table value 1.725 at significant level 95%. Conclusion: Provision nebulizer of combivent therapy provide greater effectiveness in reducing airway obstruction in asthma bronchial patients at ER ofBBKPM Makassar in 2012.